Impact Evaluation of a Large-scale Rural Sanitation Project in Indonesia - Cameron, Lisa; Shah, Manisha; Olivia, Susan (World Bank, Washington, DC, 2013)
Lack of sanitation and poor hygiene behavior cause a tremendous disease burden among the poor. This paper evaluates the impact of the Total Sanitation and Sanitation Marketing project in Indonesia, where about 11 percent of children have diarrhea in any two-week period and more than 33,000 children die each year from diarrhea. The evaluation utilizes a randomized controlled trial but is unusual in that the program was evaluated when implemented at scale across the province of rural East Java in a way that was designed to strengthen the enabling environment and so be sustainable. One hundred and sixty communities across eight rural districts participated, and approximately 2,100 households were interviewed before and after the intervention. The authors found that the project increased toilet construction by approximately 3 percentage points (a 31 percent increase in the rate of toilet construction). The changes were primarily among non-poor households that did not have access to sanitation at baseline. Open defecation among these households decreased by 6 percentage points (or 17 percent). Diarrhea prevalence was 30 percent lower in treatment communities than in control communities at endline (3.3 versus 4.6 percent). The analysis cannot rule out that the differences in drinking water and handwashing behavior drove the decline in diarrhea. Reductions in parasitic infestations and improvements in height and weight were found for the non-poor sample with no sanitation at baseline.